2005
DOI: 10.1002/prep.200500001
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared and Visible Absorption Spectroscopy of Nano‐Energetic Materials Containing Aluminum and Boron

Abstract: Near-infrared and visible absorption spectra are measured for nano-energetic materials consisting of thirteen different types of Al or B nano-particles in the 30 nm to 1 mm size range embedded in nitrocellulose or Teflon oxidizers, using an integrating sphere absorption spectrometer. The Al nano-particle absorption is generally similar to the spectra of bulk Al, but the absorption strength is size-dependent and up to twelve times more intense. Absorption coefficients are determined as a function of nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The peak absorption cross section of single particles can be calculated from the following eq , by analyzing the UV–vis absorption spectra at a known particle concentration. where α is the absorption coefficient, A is the absorbance value, L is the optical path, ρ is nanoparticle number density (i.e., the number of particles per unit volume), ρ n is the mass concentration of PFO/CN-PPV Pdots, m is the mass of a single particle, d is the mean diameter of Pdots, and ρ H 2 O is the mass density of water.…”
Section: Methodsmentioning
confidence: 99%
“…The peak absorption cross section of single particles can be calculated from the following eq , by analyzing the UV–vis absorption spectra at a known particle concentration. where α is the absorption coefficient, A is the absorbance value, L is the optical path, ρ is nanoparticle number density (i.e., the number of particles per unit volume), ρ n is the mass concentration of PFO/CN-PPV Pdots, m is the mass of a single particle, d is the mean diameter of Pdots, and ρ H 2 O is the mass density of water.…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency of absorption of the near-infra red and visible spectra by nanoparticles of Al and B embedded in nitrocellulose or Teflon oxidizers was studied in Ref. [189]. It was found that absorption strength is greater for Al nanoparticles as compared to bulk Al.…”
Section: Temperature Kmentioning
confidence: 98%
“…A methodology for studying shock initiation of thin RM layers using a very short laser pulse was developed . A picosecond laser flash heating vaporized the surface of an RM target.…”
Section: Characterization Of Rsmsmentioning
confidence: 99%